Does Daughter Deficit Promote Parental Substance Use? Longitudinal Evidence on Smoking from Rural China - Xi Chen (Institute of Labor Economics (IZA), 2017)
China and some other Asian countries have experienced skewed sex ratios, triggering intense competition and pressure in the marriage market. Meanwhile, China has more smokers than any other country, with half of men smoke while few women smoke. Men are the major income earners in most Chinese families and thus bear much of the financial burden in preparation for children's marriage. This paper investigates how a demographic factor – a large number of surplus men in the marriage market in China – affects their fathers' smoking behavior. We utilize two household longitudinal surveys as well as a random subsample of the China Population Census to examine fathers' smoking in response to skewed sex ratios. Strikingly, fathers smoke more for families with a son living in communities with higher sex ratios. In contrast, those with a daughter do not demonstrate this pattern. Coping with the marriage market pressure is a more plausible pathway linking the observed skewed sex ratios among children and intense smoking among fathers. Considering worsening sex ratios and highly competitive marriage market in the coming decade as well as lasting health impacts due to smoking, policies suppressing unbalanced sex ratios could lead to welfare gains.
Keywords: J13; D12; I19; 330; sex ratios; marriage market; paternal smoking; stress